Agricultural Waste for Electricity Production in Latin America: A Literature Review of Successful Cases in Mexico, Colombia, and Brazil) - Marín-Apolo, Yulissa del Cisne (2025)
In Latin America, various wastes offer opportunities for the generation of electric energy, promoting a more sustainable energy matrix. Given this reality, several countries in the region are undergoing an energy transition and are conducting research aimed at this objective. The research reported in this article seeks to provide an overview of the availability of agricultural waste for electricity generation. The research focuses on three Latin American countries: Mexico, Colombia and Brazil; leaders in this advancement. The main objective is to evaluate the viability and degree of use of energy resources derived from agricultural waste in each country, through a comparative analysis of data on bioenergy. The methodology includes a bibliographic review, focused on the quantity and type of agricultural waste in each country, as well as a review of existing bioenergy projects. It was found that Mexico produced between 17.5-58.1 million tons of agricultural waste annually; Colombia, around 21.54 million tons; and Brazil, with 798.34 million tons, the latter having the largest amount due to its territorial extension. This study has revealed that, although Brazil and Mexico efficiently use resources such as sugarcane bagasse, and Colombia uses palm oil to generate electricity, there are still areas for improvement in waste management.